ERWP 2021
DOI: 10.24148/wp2021-11
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Gains from Equity

Abstract: How much is inequity costing us? Using a simple growth accounting framework we apply standard shift-share techniques to data from the Current Population Survey (1990-2019) to compute the aggregate economic costs of persistent educational and labor market disparities by gender and race. We find significant economic losses associated with these gaps. Building on this finding, we consider which disparities generate the largest costs, paying specific attention to differences in employment, hours worked, educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Finally, beyond its importance to individuals, families, and communities and deep intrinsic value as a matter of human rights, ending racial discrimination in the labor market has significant implications for economies and companies. For example, in the US alone, estimates from the Federal Reserve Bank of San Francisco find that closing the racial gaps in employment-to-population ratios between 1990 and 2019 would have boosted 2019 GDP by over $150 billion (Buckman et al. , 2021), while other research has forecast that closing the racial earnings gap by 2050 would boost GDP by 22% (Turner, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, beyond its importance to individuals, families, and communities and deep intrinsic value as a matter of human rights, ending racial discrimination in the labor market has significant implications for economies and companies. For example, in the US alone, estimates from the Federal Reserve Bank of San Francisco find that closing the racial gaps in employment-to-population ratios between 1990 and 2019 would have boosted 2019 GDP by over $150 billion (Buckman et al. , 2021), while other research has forecast that closing the racial earnings gap by 2050 would boost GDP by 22% (Turner, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, beyond its importance to individuals, families, and communities and deep intrinsic value as a matter of human rights, ending racial discrimination in the labor market has significant implications for economies and companies. For example, in the US alone, estimates from the Federal Reserve Bank of San Francisco find that closing the racial gaps in employment-to-population ratios between 1990 and 2019 would have boosted 2019 GDP by over $150 billion (Buckman et al, 2021), while other research has forecast that closing the racial earnings gap by 2050 would boost GDP by 22% (Turner, 2018). Likewise, a significant body of evidence demonstrates that greater racial and ethnic diversity within companies, including on boards, improves their financial performance and degree of innovation (Erhardt et al, 2003;Herring, 2009;Cheong and Sinnakkannu, 2014;Thomas et al, 2016;Hunt et al, 2018).…”
Section: The Critical Need To Accelerate Progressmentioning
confidence: 99%
“…Several authorities have translated disparities by race into lost opportunity for the U.S. economy. Estimates suggest that addressing the earnings gap between Whites and racial minorities would help to increase U.S. gross domestic product (GDP) by 12% to 33%, creating many more opportunities for all (Buckman et al, 2021; Turner, 2016). These studies suggested that the country's economic growth could be much faster but are met with skepticism about whether these types of gains are truly possible and if so how.…”
Section: A Research Agenda To Advance the Regional Economic Developme...mentioning
confidence: 99%
“…While racial differences in the US have been analysed for many years, recent events have sparked a renewed interest in the differences in opportunities across ethnic groups (e.g.,Edwards et al, 2019). Recent work has documented how racial inequality in income and wealth continued to grow over the past decades(Bartscher et al, 2021) and how it leads to increasing macroeconomic costs(Buckman et al, 2021). Moreover, several studies in the context of the Federal Reserve's monetary policy strategy review(Aaronson et al, 2019, Feiveson et al, 2020 suggest that racial inequality interacts with monetary policy.ECB Working Paper Series No 2719 / September 2022…”
mentioning
confidence: 99%